A ligand-based system for receptor-specific delivery of proteins - Maffei, Mariano; Morelli, Chiara; Graham, Ellie; Patriarca, Stefano; Donzelli, Laura; Doleschall, Balint; de Castro Reis, Fernanda; Nocchi, Linda; Chadick, Cora H.; Reymond, Luc; Corrêa, Ivan R.; Johnsson, Kai; et al. (Scientific reports, 2019)
Gene delivery using vector or viral-based methods is often limited by technical and safety barriers. A promising alternative that circumvents these shortcomings is the direct delivery of proteins into cells. Here we introduce a non-viral, ligand-mediated protein delivery system capable of selectively targeting primary skin cells in-vivo. Using orthologous self-labelling tags and chemical cross-linkers, we conjugate large proteins to ligands that bind their natural receptors on the surface of keratinocytes. Targeted CRE-mediated recombination was achieved by delivery of ligand cross-linked CRE protein to the skin of transgenic reporter mice, but was absent in mice lacking the ligand’s cell surface receptor. We further show that ligands mediate the intracellular delivery of Cas9 allowing for CRISPR-mediated gene editing in the skin more efficiently than adeno-associated viral gene delivery. Thus, a ligand-based system enables the effective and receptor-specific delivery of large proteins and may be applied to the treatment of skin-related genetic diseases.
Gesehen am 03.12.2020